ANALYSIS OF THE EFFECT OF E-RECRUITMENT, EMPLOYER BRANDING, AND CORPORATE REPUTATION ON THE INTEREST OF GENERATION Z IN APPLYING FOR JOBS - Elisabet Putri Permatasari; Riska Fii Ahsani (Universitas Nusa Cendana, 2026)
This study investigates the influence of e-recruitment, employer branding, and corporate reputation on job application interest among Generation Z fresh graduates in Surakarta City, Central Java. Adopting a quantitative survey design, data were collected through questionnaires distributed to 60 purposively selected respondents who had completed their education and previously applied for jobs. The research instrument was tested for validity and reliability prior to analysis. Multiple linear regression was employed to examine the relationships among variables. The findings reveal that e-recruitment, employer branding, and corporate reputation each have a significant effect on job application interest. Collectively, these variables explain a substantial proportion of the variation in job application interest among fresh graduates. The results highlight the importance of digital recruitment systems and strong organizational image in attracting Generation Z job seekers. This study contributes to the literature on recruitment strategies and employer attractiveness in the digital era. Keywords: E-recruitment; Employer Branding; Corporate Reputation